Describing Scale Shape Morphology of Glossogobius Giuris using Landmark-based Geometric Morphometrics (Journal of Informatics and Mathematical Sciences, 2017)
In the conservation of biodiversity, natural resources, and fisheries management, species identification and population discrimination are necessary. In freshwater fishes, the scale morphology and squamation is important because this can be helpful in the identification of fishes up to the extensive levels of species, sex determination and pathology of fish. Glossogobius giuris is an endemic species and considered important in Balo-i, Lanao del Norte and Mandulog River in Iligan City, Philippines. It is locally known as "kadurog”. The fish is highly commercialized because it provides food for the community, thus this study was conducted. We used scale morphology to distinguish male and female of G. giuris using landmark-based geometric morphometrics. Results of the study have shown that there is no sexual dimorphism in the fish based on scale shapes. However, variations of the scales do exist within sexes based on the results of the relative warp analysis. The variations observed can be attributed to environmental factors affecting the development of the fish and thus resulting to phenotypic plasticity in the patterns of variation in the scale shapes among individuals.
Keywords: Glossogobius giuris; Geometric morphometrics; Relative warps; Phenotypic plasticity